2022
DOI: 10.2147/dddt.s367624
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of Evidence Supporting the Role of Tripterygium Glycosides for the Treatment of Diabetic Kidney Disease: An Overview of Systematic Reviews and Meta-Analyses

Abstract: Background Tripterygium glycosides (TG) is widely used in the treatment of diabetic kidney disease (DKD) in China. To systematically assess and synthesize the available evidence, we present an overview of systematic reviews (SRs) and meta-analyses (MAs) on the topic of TG interventions for DKD. Methods SRs/MAs on TG interventions for DKD were comprehensively searched in seven databases. Methodological quality, risk of bias, reporting quality, and quality of evidence wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Tripterygium and its extracts (e.g., triptolide and tripterygium glycosides) have been recognized as important therapeutic agents for clinical treatment of DKD with proved efficacy. A meta-analysis in 2,764 DKD patients from 31 articles revealed that Tripterygium Glycosides Tablet administration for 3 months significantly reduced the levels of 24-h uridine triphosphate (UTP) and serum creatinine (SCr) in DKD patients, and there was a low incidence of adverse events [ 60 ]. Another study found that tripterygium glycosides up-regulated the autophagy level and reduced the EMT and apoptosis in DKD rats through the mTOR/Twist1 signaling pathway [ 61 ].…”
Section: Advances In Chinese Medicine In Treatment Of Dkdmentioning
confidence: 99%
“…Tripterygium and its extracts (e.g., triptolide and tripterygium glycosides) have been recognized as important therapeutic agents for clinical treatment of DKD with proved efficacy. A meta-analysis in 2,764 DKD patients from 31 articles revealed that Tripterygium Glycosides Tablet administration for 3 months significantly reduced the levels of 24-h uridine triphosphate (UTP) and serum creatinine (SCr) in DKD patients, and there was a low incidence of adverse events [ 60 ]. Another study found that tripterygium glycosides up-regulated the autophagy level and reduced the EMT and apoptosis in DKD rats through the mTOR/Twist1 signaling pathway [ 61 ].…”
Section: Advances In Chinese Medicine In Treatment Of Dkdmentioning
confidence: 99%
“…Paeoniflorin, for instance, demonstrates the ability to reduce macrophage infiltration and expression of inflammatory cytokines, enhancing kidney function and ameliorating histological damage in diabetic mice kidneys ( 229 ). Tripterygium glycosides exhibit anti-inflammatory properties and effectively prevent oxidative-induced glomerular membrane rupture, consequently reducing proteinuria in glomerulonephritis and impeding DKD progression ( 230 – 232 ). While low-quality evidence suggests that Tripterygium could be a potential complementary therapy for DKD, most of these studies remain confined to the cellular, molecular, and animal levels ( Supplementary Table 2 ), with a lack of large-scale prospective studies specifically targeting tubular lesions and high-quality pathological evidence substantiating their efficacy.…”
Section: Therapeutic Targets For Renal Tubulointerstitial Lesionsmentioning
confidence: 99%
“…Tripterygium glycoside is a fat-soluble mixture extracted from Tripterygium wilfordii Hook F, which composed of diterpene lactone, alkaloid and triterpenoid (174). Tripterygium glycoside has excellent anti-inflammatory and antioxidant damage properties and is widely used in China to treat proteinuria in patients with DKD (175,176). Similarly, Tripterygium glycoside also alleviated podocyte apoptosis by upregulating autophagy through the mTOR/Twist-related protein 1 (TWIST1) signaling pathway (176) and downregulation of b-arrestin-1 (38).…”
Section: The Active Compounds In Attenuating Renal Injury Via Regulat...mentioning
confidence: 99%